Taxonomic and functional diversity of alkali-tolerant bacteria enriched from the Taklimakan Desert - Wen, Feng; Yang, Guo; Zhao, Xueling; Zhao, Tiantian; Bai, Linquan; Xia, Zhanfeng (Frontiers in Microbiology, 2025)
The Taklimakan Desert is a naturally alkaline ecosystem harboring a rich diversity of alkali-resistant microorganisms. However, systematic studies on their distribution, diversity, and biotechnological potential remain limited. In this study, five representative soil samples were collected from the central region of the Taklimakan Desert, where the original soil pH ranged from 8.78 to 9.8. To investigate the effect of alkaline conditions on microbial communities, the samples were subjected to enrichment in culture media adjusted to pH 9–11. The bacterial community structure of the enriched fraction was assessed using culture-independent 16S rRNA gene amplicon sequencing, while a non-enriched control (CK) group—consisting of the same soils without pH adjustment—was simultaneously sequenced to determine the baseline bacterial composition. In parallel, a culture-dependent approach was employed to isolate alkali-tolerant bacterial strains from the same samples using Gibbons medium at pH 9, 10, and 11. Based on distinct colony morphologies, isolates were selected, repeatedly purified by streaking, and taxonomically identified via 16S rRNA gene sequencing, resulting in a total of 291 strains. These isolates were taxonomically assigned to four phyla, six classes, 17 orders, 25 families, and 56 genera. Among them, 114 strains shared less than 98.65% sequence identity with known species, suggesting the presence of numerous potential novel taxa. Approximately 14.07 and 61.48% of the isolates were categorized as alkali-tolerant and alkalophilic, respectively, with 85 strains capable of growing under extreme conditions (pH 12 and/or 25% salinity). Functional screening revealed enzymatic activity in a substantial portion of the isolates: 20.35% produced amylase, 19.91% protease, 30.30% cellulase, and 47.61% exhibited at least one enzymatic function. Overall, this study integrates both culture-independent and culture-dependent approaches to reveal the taxonomic and functional diversity of alkali-tolerant bacteria in the Taklimakan Desert, highlighting their ecological roles and potential applications in industrial biotechnology.